2023
DOI: 10.1039/d2sc06033g
|View full text |Cite
|
Sign up to set email alerts
|

Building Streptomyces albus as a chassis for synthesis of bacterial terpenoids

Abstract: Terpenoids comprise the most chemically and structurally diverse family of natural products. In contrast to the huge numbers of terpenoids discovered from plants and fungi, only a relatively small number...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In a recent study, Hu et al demonstrated heterologous expression of ariD-G genes in S. albus J1074 M, leading to the production of a 6/10-fused eunicellane diterpenoid (9, Figure 3A), albeit without the detection of aridacins (1-3). [42] To elucidate the biosynthetic control of 6/7/5-tricyclic versus 6/10-bicyclic diterpenoids by the ari BGC, we reanalyzed the metabolites from our engineered strains. Based on HPLC-MS analysis, besides the aridacins, which were major products, S. lividans DL10011 also produced trace amounts of 8-11 (Figures 3D, S66 S13).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, Hu et al demonstrated heterologous expression of ariD-G genes in S. albus J1074 M, leading to the production of a 6/10-fused eunicellane diterpenoid (9, Figure 3A), albeit without the detection of aridacins (1-3). [42] To elucidate the biosynthetic control of 6/7/5-tricyclic versus 6/10-bicyclic diterpenoids by the ari BGC, we reanalyzed the metabolites from our engineered strains. Based on HPLC-MS analysis, besides the aridacins, which were major products, S. lividans DL10011 also produced trace amounts of 8-11 (Figures 3D, S66 S13).…”
Section: Resultsmentioning
confidence: 99%
“…(Table S16), [29] a single cyclic shunt product, resulting from the only formation of the first CÀ C bond between C1 and C14 (Figure 2C). Inspection of the crystal structure of PhmA revealed the presence of the L229 residue within the nonclassical NSE/DTE motif, which imposes steric effects on the substrate, causing it to adopt a bent conformation (Figure S14A).…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Terpenoids are the largest class of natural products that have multiple biological activities and widespread applications in pharmaceuticals, agriculture, and fragrances. 13,14 Hemiand monoterpenoids, two major types of terpenoids, which include some of the pharmaceutically important natural products, are produced from animals, plants, and microorganisms. 15 Prenylation and geranylation are two important metabolic processes that proceed under enzyme catalysis among many approaches for producing terpenoids.…”
Section: Introductionmentioning
confidence: 99%